Adubação nitrogenada e idade de corte na produção de matéria seca do capim-elefante no Cerrado - Flores, Rilner A.; Urquiaga, Segundo S.; Alves, Bruno J. R.; Collier, Leonardo S.; de Morais, Rafael F.; Prado, Renato de M. [UNESP] (Universidade Federal da Paraíba (UFPB) Ccsa, 2012)
The objective of this study was to investigate the effect of the application of N fertilizer and the cutting age on the dry biomass production of elephant grass. The experiment was performed with the variety Paraiso and planted in a Ferralsol in 2008 in the district of Gurupi (State of Tocantins). Four different rates of urea application were tested (0, 50, 100 and 150 kg ha(-1)) and harvests were made at 120, 150 or 180 days after germination (DAG) of the setts. The dry matter and total N accumulation were evaluated. Dry matter production increased with dose of N, the greatest effect being observed at 180 DAG. There was a linear increase in dry matter (R-2 = 0.75**) and N accumulation (R-2 = 0.96**) permitting a productivity of 34 t ha(-1) of dry matter and an accumulation of 471 kg N ha(-1). The N utilization efficiency (biomass production per unit of applied N) increased with plant age. The higher efficiency of N use favored the quality of biomass production for energy production owing to the higher fibre content.
Effect of nitrogen fertilizer and cutting age on the dry matter production of elephant grass in Savana
Keywords: Pennisetum purpureum; biomass; bioenergy